The Application of water pump based dc solar cells as the raw water to wash vehicle business - Assiddiq S, Hasbi; Busran (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2024)
Water needs to venture vehicle laundering enough business owners try to find alternative solutions through building wells as a principal source of raw water to wash cars, but did not have the technology entrepreneurs will to move water from wells to storage.The event was held uses experimental methods through the system design, the process of making and testing system to move water from wells to shelter raw water business of vehicles. Students projects creativity result for innovative works shows that the output of solar cells can be sufficient to conduct charging lithium battery power 12 V 100 Ah for one day with a note that the intensity of the sun under normal circumstances in other words not overcast or rain, lithium battery power use 12 V 100 Ah when full to the empty with a water pump dc 12 V 180 W to move water from wells to shelter during 4,75 hours. The results of the innovative works students creativity program that is carried out by students year 2024 engineering course kotabaru polytechnic positive impact to business players laundering vehicle especially in moving water from wells to a kind of water body.